Pengaruh Kepemimpinan Transformasional Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan Pada PT. Transco Energi Utama POM - Lidya Martha; Oki Nalia Fartika (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect oftransformational leadership and non-physical workenvironment on employee performance at PT.Transco Energi Utama POM. The sample in thisstudy amounted to 87 employees. The research datawere collected from the results of multiple linearregression analysis and hypothesis testing. Theresults of this study indicate that transformationalleadership has a positive and significant effect onemployee performance, and the non-physical workenvironment has a positive and significant effect onemployee performance. It can be seen that thesignificant value of transformational leadership andnon-physical work environment on employeeperformance is the value 0.000 <0.05 and the t countis 3.637 from the t table 1.988.